Cognitive behavior counseling to help victims of cyberbullying: systematic review - Febri Wandha Putra; M Ramli (Konselor, 2022)
The impact of technological advances is bullying on social media. As a result of bullying that occurs on social media, many individuals, especially students, are victims. The symptoms possessed by victims of cyberbullying are; feel anxiety, stress, depression, decreased learning motivation, withdraw from the social environment. One of the counselor's efforts in helping victims of cyberbullying is to provide cognitive behavior counseling. This type of research is a qualitative research using a systematic review literature review approach. The steps in the implementation of cognitive behavior counseling are; 1) identify students who are victims, 2) apply a cognitive behavior approach to the counseling process and 3) follow up.